Beyond the plantation: Palm oil as a strategic lever for regional development and economic transformation growth in Indonesia - Judijanto , Loso (Growth, 2025)
Indonesia’s palm oil industry is a key driver of national and regional economic growth, particularly benefiting rural and underdeveloped areas. This study aims to synthesise the constructive contributions of palm oil to local economies by assessing its impact on household income, employment, infrastructure, and regional development. Employing a qualitative integrative literature review, the research systematically analyses over 80 peer-reviewed articles, reports, and academic sources from major databases using thematic content analysis. The findings reveal that palm oil cultivation has significantly increased household incomes, often doubling or tripling them compared to other crops, created over four million direct jobs, and spurred infrastructure improvements such as roads, schools, and healthcare facilities. These developments have contributed to poverty reduction and enhanced social mobility in remote regions. However, the benefits are not uniformly distributed, with smallholders and certain regions receiving a smaller share of economic gains, and persistent challenges related to environmental sustainability and social equity. The practical implications suggest that to sustain and broaden these positive outcomes, policy interventions should prioritise inclusive benefit sharing, support for smallholders, and the adoption of sustainable practices. Strengthening governance and promoting responsible certification schemes are essential to ensure that the palm oil sector continues to drive equitable and sustainable economic transformation in Indonesia.